The nutritional status of healthy children using bioelectrical impedance and anthropometric measurement - Paweł Więch; Izabela Sałacińska; Michał Bączek; Dariusz Bazaliński (Elsevier, 2022)
Objective: Monitoring of healthy children should include precise assessment of their nutritional status to identify children and adolescents at risk of nutrition disorders. Therefore, the aim of this study was to assess the nutritional status of healthy children using different nutritional risk screening tools. Method: The study sample consisted of 550 participants within the age range of 7-15 years. Anthropometric characteristics (body mass, height, body mass index) were collected using standard procedures. In addition, the following parameters were analyzed: fat mass, fat-free mass, body cell mass, and total body water. Results: The results revealed that variables such as children's age and sex significantly differentiated the values of selected components of the body composition. Conclusions: This observation suggests that it is necessary to use different methods to evaluate nutritional status among healthy children.